Mediating role of blood pressure on the association of body mass index with cardiovascular disease risk - Zeng-hang ZHANG; Xiao-lei GUO; Zhao-xue YIN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate mediating role of blood pressure on the association of body mass index (BMI) with cardiovascular disease (CVD) risk and to provide evidence for control of CVD risk. MethodsUsing stratified multistage random sampling and a self-designed questionnaire, a baseline survey including face-to-face interview, physical examination and laboratory tests were conducted among 15 600 permanent urban/rural residents aged 18 - 69 years during June - September, 2021 in Shandong province; then the residents were followed up to October 11, 2021 through the Cardiovascular Diseases and Mortality Surveillance System to collect the information on the prevalence of CVD. Univariate and multivariate Cox proportional risk regression model was used to analyze the association of body mass index (BMI) with the risk of CVD. The dose-response relationship between BMI and CVD risk was described with restricted cubic splines (RCS). The mediating role of blood pressure on the association of BMI with CVD risk was assessed with sequential test. ResultsOf all the residents at the baseline survey, 89.17% (13 688) were followed up; after excluding those with previous history of coronary heart disease (n = 254) and stroke (n = 115) and those without valid outcome information, 13 268 participants were finally included in the analysis, with a total follow-up of 133 733.79 person-years and a median follow-up period of 10.25 years. By the end of the follow-up among the participants, totally 492 CVD incidences were identified and the CVD incidence density was 367.90/100 000 person-years. The number of CVD incidence was 22，173，183, and 114 among the participants with low-weight, normal-weight, overweight, and obesity, with the corresponding CVD incidence densities (1/100 000 person-years) of 380.08, 285.84, 410.42, and 499.25, respectively. After adjusting for age, gender, education, marital status, annual household income, living area (urban/rural), geographical region of residence (central/southeast/northwest), smoking, alcohol drinking, physical activity, daily salt intake, daily oil intake, and disease history of hypertension, diabetes or dyslipidemia, multivariate Cox proportional risk regression model analysis showed that the participants with overweight were at an increased risk of CVD incidence (hazard risk [HR] = 1.253, 95% confidence interval [95% CI]: 1.014 - 1.548) compared to those with normal weight. Dose-response analysis revealed a J-shaped relationship between BMI and the risk of CVD (χ2overall = 29.87, P overall = 0.004; χ2nonlinear = 7.08, Pnonlinear = 0.069). Mediating effect analysis demonstrated that the direct effect of BMI on CVD incidence risk was 0.038 (Z = 11.644, P < 0.001) and the mediating effect of systolic blood pressure (SBP), diastolic blood pressure (DBP) and hypertension was 0.022 (Z = 12.354, P < 0.001), 0.041 (Z = 10.589, P < 0.001) and 0.133 (Z = 11.506, P < 0.001). The mediating effect percentages of SBP, DBP pressure and hypertension were 36.67%, 51.90% and 77.78%, respectively. ConclusionBlood pressure has a strong mediating effect on the association of BMI with CVD risk. The results suggested that more attention and intervention on the changes of blood pressure need to be promoted among overweight and obesity populations.